Managing the world: Conceptions of imperial rule between republicanism and technocracy - Hausteiner, Eva Marlene (History of European Ideas, 2016)
The article examines a technocratic vision of empire arising in Britain in the late nineteenth and early twentieth centuries and its implications for the theorization of empires, the legitimation of large-scale political orders, and their spatial imagination. The role of the Roman model for the British in the decades after 1870 as a resource of policy advice, legitimation, and identity-building serves as a case study for analyzing the role of historical precedence for imperial elites. This analysis opens the perspective onto a notion of empire that significantly differs from the one discussed in recent debates on liberalism and empire: British political actors and observers delineate a concept of empire that is not universalist, but heterogeneous, hierarchical, and technocratic.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Britain; Empire; Republicanism; Rome; Technocracy